Comparing two federal financing strategies on penetration and sustainment of the adolescent community reinforcement approach for substance use disorders: protocol for a mixed-method study - Alex R. Dopp (Implementation Science Communications, 2022)
Abstract Background Sustained, widespread availability of evidence-based practices (EBPs) is essential to address the public health and societal impacts of adolescent substance use disorders (SUD). There remains a particularly significant need to identify effective financing strategies, which secure and direct financial resources to support the costs associated with EBP implementation and sustainment. This protocol describes a new project comparing two types of U.S. federal grant mechanisms (i.e., a type of financing strategy), which supported the implementation of the Adolescent Community Reinforcement Approach (A-CRA) EBP for SUD, through either organization-focused or state-focused granting of funds. The Exploration-Preparation-Implementation-Sustainment (EPIS) framework will guide our study aims, hypotheses, and selection of measures. Method We will employ a longitudinal, mixed-method (i.e., web surveys, semi-structured interviews, document review, focus groups, administrative data), quasi-experimental design to compare the grant types’ outcomes and examine theoretically informed mediators and moderators. Aim 1 will examine the proportion of eligible clinicians certified in A-CRA with adequate fidelity levels (i.e., penetration outcomes) at the end of grant funding. Aim 2 will examine the sustainment of A-CRA up to 5 years post-funding, using a 10-element composite measure of treatment delivery and supervision activities. We will integrate the new data collected from state-focused grant recipients (~85 organizations in 19 states) with previously collected data from organization-focused grant recipients (Hunter et al., Implement Sci 9:104, 2014) (82 organizations in 26 states) for analysis. We will also use sensitivity analyses to characterize the effects of observed and unobserved secular trends in our quasi-experimental design. Finally, aim 3 will use comparative case study methods (integrating diverse quantitative and qualitative measures) to identify and disseminate policy implications about the roles of state- and organization-focused federal grants in efforts to promote adolescent SUD EBP implementation and sustainment. Discussion The proposed research will have direct, practical implications for behavioral health administrators, policymakers, implementation experts, and the public. It will offer new knowledge that can directly inform financing strategies to support large-scale, sustained EBP delivery in behavioral health—while advancing implementation science through the use of novel methods to study financing strategies and sustainment.